The God who is beauty : beauty as a divine name in Thomas Aquinas and Dionysius the Areopagite - Sammon, Brendan Thomas (Eugene, Oregon : Pickwick Publications, 2013)
In the beginning was beauty, and beauty was with God, and beauty was God. If the tradition of divine names, that (in its Christian form) originates with Dionysius the Areopagite and includes among its ranks Albert the Great, Thomas Aquinas, and others, is correct in identifying God with the name beauty, then repurposing the Prologue to John's Gospel in this way seems hardly controversial. For if beauty is a divine name then not only is it fitting to say God is beautiful, but it is equally fitting to say that God is beauty itself. However, like most arguments from fittingness-that is to say, ar.
Beauty and the divine in ancient Greek philosophy: Plato and Aristotle -- Beauty and the divine in Neoplatonism: Plotinus and Proclus -- The tradition of the divine names -- Beauty as a divine name in Dionysius the Areopagite I: beauty as transcendent plenitude -- Beauty as a divine name in Dionysius the Areopagite II: beauty as a principle of determination / Beauty and the one -- The passage of Dionysius into the Latin West -- The journey of beauty as a divine name: from the sixth to the thirteenth century -- Beauty as a divine name in Albert the Great -- Thomas Aquinas and the tradition of the divine names -- Beauty as a divine name in Thomas Aquinas: In de divinis nominibus expositio -- Beauty as a divine name in Thomas Aquinas: beyond the commentary on the divine names -- Conclusion. Beauty as the between.
Includes bibliographical references (pages 371-387) and index.
Print version record.
Keywords: Pseudo-Dionysius, -- the Areopagite -- Aesthetics; Thomas, -- Aquinas, Saint, -- 1225?-1274 -- Aesthetics; Aesthetics -- Early works to 1800.; Aesthetics -- Religious aspects -- Christianity; God -- Beauty; God -- Name -- History of doctrines; Aesthetics -- Early works to 1800.; Aesthetics -- Religious aspects -- Christianity; God -- Beauty; God -- Name -- History of doctrines; Pseudo-Dionysius, the Areopagite -- Aesthetics; Thomas, Aquinas, Saint, 1225?-1274 -- Aesthetics; RELIGION -- Christian Theology -- General; Electronic books